Expression of acetylated histones H3 and H4 and histone deacetylase enzymes HDAC1, HDAC2 and HDAC6 in simple mammary carcinomas of female dogs - Senhorello, Igor Luiz Salardani; Matiz, Oscar Rodrigo Sierra; Canavari, Isabela Cristina; Hernandez, Giovanny Vargas; Anai, Letícia Abrahão; Navarrete Ampuero, Roberto Andrés; Pazzini, Josiane Moraes; Prado, Cibele Maria; Meirelles, Flavio Vieira; Vasconcelos, Rosemeri de Oliveira; Tinucci-Costa, e Mirela (Frontiers in Genetics, 2023)
Histone deacetylation is an important mechanism involved in human breast cancer tumorigenesis and recent veterinary oncology studies also demonstrate a similar relationship in some canine neoplasms. The use of HDAC inhibitors in vitro and in vivo has demonstrated antitumor action on several strains of human and animal cancers. The present study aims to correlate the expression of H3K9Ac, H4K12Ac, HDAC1, HDAC2 and HDAC6 in simple mammary carcinomas in dogs with clinicopathological parameters and overall survival time. To this end, 61 samples of simple breast carcinomas were analyzed by the immunohistochemistry technique with subsequent validation of the antibodies by the Western Blot technique. The expressions obtained via a semi-quantitative way were categorized by assigning scores and classified into high or low expressions according to the given score, except for HDAC6, when the marking percentage was considered and subdivided into high and low expressions using the median value. For statistical analysis, the chi-square test or Fisher exact test were used as univariate analysis and correspondence analysis as a multivariate test, in addition to the Kaplan-Meier survival analysis. In the studied samples, the highest frequencies were determined for the high expression proteins H4K12Ac (88.5%), HDAC2 (65.6%) and HDAC6 (56.7%) and the low expression proteins H3K9Ac (73.8%) and HDAC1 (54.1%). An association between the low expression of HDAC1 and the presence of lymph node metastasis (p=0.035) was indicated by univariate analysis while the high expression of HDAC1 was associated with favorable prognostic factors, such as the absence of lymph node metastasis and low mitotic index by multivariate analysis. Also, by multivariate analysis, the low expression of HDAC6 was correlated with the low expression of Ki67, smaller tumors, and better prognosis factors as well. Protein expression was not correlated with patients' overall survival time (p>0.05). The high expressions of HDAC2 and HDAC6 in mammary carcinomas in female dogs may be useful information for research involving therapeutic targets with iHDACs since their inhibition favors hyperacetylation and transcription of tumor suppressor genes.